2022
DOI: 10.3390/ijms231911080
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells and Dendritic Cells as Cellular Immune Checkpoints in Immunotherapy of Solid Tumors

Abstract: The immune checkpoint inhibitors have revolutionized cancer immunotherapy. These inhibitors are game changers in many cancers and for many patients, sometimes show unprecedented therapeutic efficacy. However, their therapeutic efficacy is largely limited in many solid tumors where the tumor-controlled immune microenvironment prevents the immune system from efficiently reaching, recognizing, and eliminating cancer cells. The tumor immune microenvironment is largely orchestrated by immune cells through which tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 180 publications
0
6
0
Order By: Relevance
“…A previous study showed that tumor-infiltrating mast cells colocalize with regulatory T cells, coincide with local reduction of MHC-I and CD8 T cells, and is associated with anti-PD-1 resistance, which can be reversed by c-kit inhibitor treatment. At present, some studies suggested that MCs possess enormous capabilities to shape the immune microenvironment ( 48 , 49 ) and are becoming a new player in the field of cancer immunotherapy, depletion of these cells or downregulation of their functions in the TME can help break tumor resistance to anti-PD-1 therapy ( 50 ). Accordingly, we speculate that the TME prognostic model may affect BC survival outcomes by reshaping the tumor immune microenvironment, such as altering ECM, CD8+ T cell and these above-mentioned immunosuppressive cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that tumor-infiltrating mast cells colocalize with regulatory T cells, coincide with local reduction of MHC-I and CD8 T cells, and is associated with anti-PD-1 resistance, which can be reversed by c-kit inhibitor treatment. At present, some studies suggested that MCs possess enormous capabilities to shape the immune microenvironment ( 48 , 49 ) and are becoming a new player in the field of cancer immunotherapy, depletion of these cells or downregulation of their functions in the TME can help break tumor resistance to anti-PD-1 therapy ( 50 ). Accordingly, we speculate that the TME prognostic model may affect BC survival outcomes by reshaping the tumor immune microenvironment, such as altering ECM, CD8+ T cell and these above-mentioned immunosuppressive cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“…CD4( +) T memory cells have already been reported to confer vital functions on malignancy immune regulation, including participating in the activation of CD8 + T and NK killing cells, involving in the tumour immunological reactions [ 60 , 61 ]. And mast cells were reported to be able to not only influence tumor expansion via inducing angiogenesis and changing tumor extracellular matrix composition, but also could influence the infiltration and activity of dendritic cells, tumor-associated macrophages and lymphocytes, promoting pro-inflammatory reactions in tumor microenvironment [ 47 , 62 , 63 ]. The association between the signature and immune checkpoints expression as well as different immune cells infiltration, suggesting the stronger immunosuppressive environment in high-risk groups of patients comparing to low-risk group, highlighting the potential of this group to benefit from further clinical immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This challenge calls for a sophisticated harnessing of immune cells, such as the tumor-resident mast cells (MC), whose biological function can be programmed. MCs infiltrate the TME with a not yet fully developed or matured phenotype that can be influenced by the surrounding milieu ( 22 ) to play a protumorigenic ( 23, 24 ) or an antitumorigenic role ( 25 ), which can involve interaction with CAFs ( 26 ). Upon activation, MCs release secretory granules containing mediators that influence adaptive immune responses, ECM remodeling, and angiogenesis ( 27–31 ).…”
Section: Introductionmentioning
confidence: 99%